The impact of the COVID-19 Pandemic on Language Teaching in Higher Education, CercleS survey - Schaffner, Sabina; Stefanutti, Isabella (Verbum, 2022)
In March 2020, the COVID-19 pandemic forced a move online of language teaching in Higher Education (HE). The CercleS survey on the impact of the COVID-19 Pandemic on language teaching in HE aimed to study teachers’ reflections on teaching during the pandemic and on the future of foreign language instruction. Data was collected between March and May 2021, and the answers reflect the voices of 725 teachers from CercleS member institutions of both national associations and associate members. The survey was written using a mixed method approach, based on a pragmatic epistemology. The findings indicate that the teachers moved flexibly into the online mode of teaching despite limitations in technological resources and the absence of training. Learning outcomes were met, and language skills were effectively taught, except for speaking skills. Generally, the respondents see the benefits of a blended/hybrid mode of instruction. Implications for teaching practices and stakeholders are as follows: develop guidelines and training for sustainable online and hybrid teaching; negotiate conditions needed to carry out efficient and sustainable language teaching with university management; and develop international collaboration between LCs in HE.
Keywords: COVID-19 pandemic; language centres; online teaching/learning; teachers